Outstanding Low‐Temperature Performance of Structure‐Controlled Graphene Anode Based on Surface‐Controlled Charge Storage Mechanism. (29th January 2021) - Lee, Michael J.; Lee, Kyungbin; Lim, Jeonghoon; Li, Mochen; Noda, Suguru; Kwon, Seok Joon; DeMattia, Brianne; Lee, Byeongyong; Lee, Seung Woo
Abstract: The energy and power performance of lithium (Li)‐ion batteries is significantly reduced at low‐temperature conditions, which is mainly due to the slow diffusion of Li‐ions in graphite anode. Here, it is demonstrated that the effective utilization of the surface‐controlled charge storage mechanism through the transition from layered graphite to 3D crumpled graphene (CG) dramatically improves the Li‐ion charge storage kinetics and structural stability at low‐temperature conditions. The structure‐controlled CG anode prepared via a one‐step aerosol drying process shows a remarkable rate‐capability by delivering ≈206 mAh g –1 at a high current density of 10 A g –1 at room temperature. At an extremely low temperature of −40 °C, CG anode still exhibits a high capacity of ≈154 mAh g –1 at 0.01 A g –1 with excellent rate‐capability and cycling stability. A combination of electrochemical studies and density functional theory (DFT) reveals that the superior performance of CG anode stems from the dominant surface‐controlled charge storage mechanism at various defect sites. This study establishes the effective utilization of the surface‐controlled charge storage mechanism through structure‐controlled graphene as a promising strategy to improve the charge storage kinetics and stability under low‐temperature conditions. Abstract : A structure‐controlled crumpled graphene anode prepared via a one‐step aerosol drying process exhibits a remarkable rate‐capability and cycling stability under extremely low‐temperature conditions. Density functional theory computations and electroanalysis elucidate that the superior low‐temperature performance of crumpled graphene anodes stems from the improved utilization of the surface‐controlled charge storage mechanism through reversible lithium‐ion adsorption on the defect sites of graphene.